Ethiek van de lectuur. Frans Kellendonk en de (h)erkenning van de andersheid - Sergier, Matthieu (Academia Press, 2012)
To what extent is it possible for a literary text to contribute to the ethical development of its reader? This book tries to provide readers with a nuanced answer to this question, as well as with methodological premises to bring to light the ethical effects of a literary text. The novels of the Dutch author Frans Kellendonk (1951-1990) offer insightful contexts and questions related to this issue. Kellendonk is one of the most controversial Dutch writers of the end of the twentieth century. Today, he is mainly considered as a kind of prophet that advocated a certain scepticism towards a multicultural society. Kellendonk's novels systematically put into question one-way interpretations of their works. They invite readers to find other interpretations, putting into question the simplifying conceptual framework that has shaped the author's posture until now. They also lay the foundations for an ethics of reading that relies on the very diegetic world to which the reader can adjust his/her own reading. This ethics is more specifically an invitation to recognize the undecidability that every reading entails.